Cognitive and Spiritual Approaches To Qur’anic Memorization: A Study of The Yadain Method in Yogyakarta - Agustono, Ihwan; Firdaus, Hajjar Darissalamah (Al Muhafidz: Jurnal Ilmu Al-Qur'an dan Tafsir, 2025)
This paper examines the contemporary process of Qur'anic memorization in Indonesia using the Yadain Method, which integrates traditional memorization practices with modern cognitive strategies. The background of this study highlights the need for innovative approaches to enhance both the intellectual retention and spiritual understanding of the Qur’an in diverse age groups. The objective is to analyze how the Yadain Method, emphasizing visualization and tadabbur (reflective contemplation of meanings), contributes to effective and holistic Qur’anic memorization. Employing a case study qualitative method, the research explores the implementation and impact of the method on participants at the Executive Tahfidz Center Yogyakarta. Key components of the method include cognitive aids such as color-coded visualizations and structured exercises, which facilitate rapid memorization and long-term retention. The findings reveal that this approach not only improves memorization efficiency but also fosters mental tranquility and spiritual growth, benefiting learners across various educational levels. The study introduces a novel framework for Qur’anic memorization in Indonesia, combining cognitive techniques with psychological and spiritual support, thus demonstrating its flexibility and effectiveness as a modern pedagogical tool.